Evaluation of Cases Had Stab Wound Injuries, 2013 -2017 - Kaya, Kenan; Akgündüz, Eren; Yılmaz, Kemal; Şeker, Zeynep; Hilal, Ahmet; Çekin, Necmi (International Journal of Innovative Research in Medical Science, 2019)
Background: Sharp objects (SO) are widely used today for various purposes in homes and workplaces. These tools are always at hand a solitary appliance or method does not require criminal sanctions unless they are misused, but they are quite often used for attack, self-defense and even to kill. Objective: The injuries and deaths caused by sharp objects have an important place in the practice of forensic medicine. Design: Retrospective review of medical reports. Setting: Auniversity hospital, Turkey. Patients and Methods: A total of 2464 cases with penetrating stab wound, whose forensic report was arranged at the Forensic Medicine Department of Cukurova University Faculty of Medicine between 2013-2017, were examined retrospectively. Results: While 90% (n: 2219) of the cases were male, 10% (n:245) were female. The average age was 28.1, the youngest patient was 5 years old and the oldest patient was 88 years old. Total 935 cases (37.9%) were between 11 and 20 years old, the highest number of cases was seen in July with 298 cases (12.1%) and 284 cases (11.5%) were exposed to life-threatening conditions. When injuries were examined according to body regions; extremity injuries were in the first place with 1541 cases (62.5%). When cases were evaluated in terms of number of lesions; it was detected that single lesion was in the first place with 1479 cases (60%) and 53.1% (n:1308) of cases were injured from their left side. Among life-threatening injuries; thorax was in the first place with 118 cases (41.5%). Conclusions: Injuries due to sharp objects come in the first place among penetrating injuries. Deaths can be seen as a result of injuries they cause in vital organs. Especially the depth of the wound trace, if injury to muscle-fascia is noted on the forensic report is important when it is necessary to decide the weight of injury, problems arise when the '' the first examining and treating physician skips detailed identification''. It would be appropriate for the physicians involved in emergency intervention to be informed of this.